Double hit: Evans syndrome after malignant thymoma treatment and parvovirus B19 infection. Issue 3 (18th March 2020) - Xie, John; Chaaya, Gerard; Jetly-Shridhar, Rachna; Atkinson, Thomas Stewart
Abstract : Malignancies are often associated with autoimmune diseases, which are addressed by treating the underlying cancer. However, there are rare malignancies that can cause autoimmune diseases even after appropriate treatment. Our patient is a 39-year-old Hispanic man with a malignant thymoma recently treated with chemotherapy and radiation who presented with syncope and dyspnoea. He was found to be both anaemic and thrombocytopenic. His labs were consistent with autoimmune haemolytic anaemia (AIHA), except his reticulocyte count was unexpectedly low. Bone marrow biopsy supported a diagnosis of Evans syndrome, a rare autoimmune condition characterised by (AIHA) combined with immune thrombocytopenia. He was also found to have an acute parvovirus B19 infection. He was treated with steroids and RBC transfusion. His blood counts gradually returned to baseline, with improvement in symptoms. This patient's thymoma treatment and active parvovirus B19 infection likely both played a role in the development of Evans syndrome.